Kerjasama Orang Tua dan Guru dalam Meningkatkan Motivasi Belajar Peserta Didik - Rofiatun Nisa'; Eli Fatmawati (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2020)
This study aims to determine the form of cooperation between parents and teachers, as well as the efforts made by parents and teachers in collaborating to increase student motivation at MI Ihyaul Ulum Manyar Sekaran Lamongan. In this study, researchers used a descriptive qualitative approach. Collecting data using interview techniques, observation and documentation techniques. The data analysis carried out in this study is in three ways, namely data reduction, data presentation and data verification. To test the validity of the data, researchers used source triangulation and method triangulation. Based on the results of data analysis, the form of cooperation between parents and teachers in increasing students' learning motivation, namely: exchanging information, either directly meeting at school or at home or by giving news using cellphones; the teacher liaison book provides information about the development of students; Communication between parents and other teachers is through recitation which is done regularly once a month. The efforts made by teachers and parents in collaborating to improve students' learning motivation, namely providing the best service to parents of students, equating the perceptions and values ​​instilled in madrasas with the values ​​taught by parents by communicating at the beginning of the meeting and provide opportunities for parents of students to be involved.